(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Human microbiome is a significant point of contact for immunity building and prevents contagious diseases. If the microbiome is disrupted, especially due to broad-spectrum antibiotics, it will make infections more likely to occur with complex disease outcomes like Clostridium difficile colitis. Pharmacological interventions such as probiotics, prebiotics, and microbiome therapy strategies one to two generations ahead and the transplant method, FMT, are all very promising solutions for infection prevention and treatment through their effects on the microbiome. The purpose of this review is to evaluate the present state of knowledge concerning the relationship between the microbiome and infections and to present some of the new pharmacological microbiome modulation strategies. It gives examples where microbiome-targeted therapy has led to a reduction in the infectious risk, a very welcome situation regarding hospitalized/immunocompromised patients, for instance. Nevertheless, though a lot of people are fascinated by the area, problems such as personalized varieties one by one, institutional prejudices, and regulatory unknowns are still the main issues for clinical translating. The use of microbiome-modulating clinical practices is backed up by the research that goes with infectious disease therapies. These fields’ growth will necessarily involve collaboration among scientists from different areas and massive error-free clinical trials to confirm the effectiveness and safety of the treatments in different subcategories of patients and infection strains.